Republic of Congo : Report on Progress Toward Meeting the Completion Point Triggers Under the Enhanced Heavily Indebted Poor Countries Initiative. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This paper discusses the Republic of Congo's enhanced Heavily Indebted Poor Countries (HIPC) initiative. If the Republic of Congo is to effectively use the resources generated by the oil windfall to reduce poverty and ensure sustainable and equitable growth, improved prioritization of public investment resources and improved project management practices are required. The establishment of institutional structures to monitor reforms is a key test of the resolve of the government to meet the HIPC triggers.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet